Low acid detergent lignin oat hull: molecular marker development and chromosome location - Rossnagel, Brian; Eckstein, Peter; Williams, Shane; Arganosa, Gene; Kibite, Solomon; Scoles, Graham (MTT, 2004)
Selection for low acid detergent lignin (ADL) hull is one way to significantly improve the feed quality of oat for ruminants. Low ADL hull in the variety AC Assiniboia was reported by Thompson et al. (2000), and subsequent research indicated that the low ADL trait was simply inherited (Williams et al. 2002). The simple inheritance and difficult phenotypic evaluation make this trait an excellent candidate for molecular marker-assisted selection (MMAS). A population of 103 recombinant inbred lines was created from the cross between AC Assiniboia and the normal ADL breeding line OT775 (from the AAFC Lacombe oat R&D program). The population was grown in replicated field trials at Saskatoon in 2000 and 2001. % ADL was determined using an ANKOM200 fiber anaylser. Molecular marker analysis was performed using bulked-segregant DNA and Random Amplified Polymorphic DNA techniques. Random primer OPD15 (CATCCGTGCT) amplified a 1020 bp fragment from DNA of normal ADL lines only and is loosely linked (~ 24 cM) in repulsion with the low ADL trait. The same polymorphic fragment maps to linkage group 24_26_34 (Kanota/Ogle) between loci cdo353a and re2M2_12x. In the test population, low ADL lines were associated with brown hull colour. This relates well with a hull-colour locus located on the same linkage group approximately 30 cM from OPD15. Mapped markers in this region are being tested for tighter linkage with low ADL, and may be converted to PCR-based markers for MMAS. RFLP marker cdo373, which is close to the mapped hull-colour locus and ~25 cM from low ADL, has been isolated and sequenced from both low and normal genotypes. Conversion of this marker, and/or others, to PCR-based markers for MMAS is in progress. Thompson et al. 2000. Canadian Journal of Animal Science 80:377-379; Williams et al. 2002. In: Proceedings (CD-ROM) of the Soils and Crops Workshop, Univ. of Saskatchewan, Saskatoon, SK, Canada. March 2002.
Keywords: Ka; oat hull; molecular marker; low lignin; mapping